Construction of Sumah Li'an Based on Sharia Maqashid - Imaro Sidqi (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
Li'an is one of the reasons for divorce that has been legitimized by Islamic law through the Qur'an and Hadith. In the Indonesian context, li'an is also described in the Compilation of Islamic Law. The problem that arises in the text of li'an law is the emergence of misogynistic interpretations, both at the conceptual and practical levels. This is contrary to the spirit behind the historical side of the revelation of the li'an verse which is intended to complain about the fate of women from accusations. This research aims to explore the concept of li'an according to the Koran in the context of the modern era using the maslahah approach by Imam al-Ghazali. The method used is literature with a qualitative descriptive type. The primary data is in the form of the Qur'an, while the secondary data is in the form of commentaries, books, journal articles, and other written sources related to the li'an theme. The results showed that the revelation of the li'an verse was a solution that responded to the problems of society at that time, namely to maintain the sanctity of lineage or lineage. With the development of technology and the dynamics of the times, technology can broaden views so that the construction of li'an law becomes relevant. Judging from the Li'an case itself, the assistive sciences that can be used include medical science. The harmonization between fiqh and modern scientific disciplines is aimed at achieving benefits in the form of maintaining religion, soul, mind, lineage, and property.Keywords : Li'an; Magna Cum Maghza; Maslahah